(untitled) (Hilo Analítico, 2022)
This article aims to raise the impact that COVID-19 has left and will leave in indirect victims; understanding these as relatives of those who died from this cause and health personnel who treated the infected, understanding this from the point of view that one of the main consequences is guilt, and how we can understand this from the postulates of Psychoanalysis . The possible implications of the feeling of loneliness that infected people may face are also mentioned; pointing out that this feeling can affect the recovery process of these. Finally, as mentioned above, it presents a challenge, mainly, for the future for people in Mental Health.